Removal of crystal violet from aqueous solution using banana peel - Lam, Coke Ying (2020)
In this study, banana peel powder (BPP) was used as the natural and affordable adsorbent for the removal of Crystal violet (CV) in aqueous solution. BPP was characterized and analyzed with Atomic Force Microscopy (AFM), Scanning Electron Microscopy (SEM) and Fourier-Transform Infrared Spectroscopy (FT-IR). Batch adsorption conditions include biosorbent dosage, initial pH and initial dye concentration with contact time. An increase in BPP dosage facilitated percentage of CV dye removal due to availability of adsorption sites. The percentage of removal was the highest at pH 4, resulting from electrostatic attraction between cationic CV dye and anionic BPP surface. CV dye uptake by BPP was significantly higher in the early stage and achieved equilibrium at 120 minutes for all dye concentrations. The CV adsorption onto BPP followed the pseudo-second-order kinetic mechanism. Results revealed that the equilibrium data was described by Freundlich isotherm model with a correlation coefficient close to unity and a maximum adsorption capacity of iii 2.5763 mg/g. Properties such as abundance, effectiveness, low-cost and non-toxicity made BPP a potential biosorbent in removing CV from wastewater.